Landscape of p53/TP53 in gastric carcinogenesis and precancerous lesions - Weihan Zhao; Xiaoquan Du; Luying Yi; Le Yu; Li Liu (Medicine, 2026)
Background: Gastric precancerous lesions (GPL) represent defined intermediate stages in the multistep cascade of gastric carcinogenesis leading to gastric cancer (GC). The literature identifies TP53 mutations as a decisive genomic event driving the transition from dysplasia to invasive malignancy. Moving beyond simple trend analysis, this study maps a knowledge architecture of p53/ TP53 across the GPL-GC continuum. We delineate institutional and international collaboration networks and trace the evolutionary trajectory of research hotspots to elucidate the intellectual landscape of this field. Methods: A bibliometric analysis was conducted using data retrieved from the Web of Science Core Collection (WoSCC). Data processing and visualization were conducted using advanced bibliometric tools, including the R package “bibliometrix,” VOSviewer, and CiteSpace. Results: A total of 442 articles were analyzed, accumulating 13,099 cited references. Bibliometric mapping identified China as the leading contributor by volume, whereas Seoul National University (South Korea) ranked highest in institutional output. In terms of dissemination, the World Journal of Gastroenterology demonstrated high productivity coupled with significant citation impact. Key contributors included Woo Ho Kim, Johan G.A. Offerhaus, and Eiichi Tahara. Keyword co-occurrence analysis delineated that early research focused on the foundational exploration of gene mutations and oncogenes, emphasizing “gene mutations” and “oncogenes.” In contrast, recent literature exhibited a shift toward predicting clinical prognosis, with high-frequency keywords such as “poor prognosis,” “epidemiology,” and “metastasis.” Conclusions: This bibliometric analysis reveals a three-stage evolution: from genomic instability to Helicobacter pylori (H. pylori )-driven carcinogenesis, and finally to prognostic stratification. This study also highlights a pivotal shift toward early-stage lesions. The field shows increasing attention to clinically oriented topics, suggesting that future studies may further explore how TP53 status can be linked with lesion staging and surveillance-oriented risk stratification.